Inventarisasi tumbuhan paku (Pteridophyta) pada Arboretum (Forested Area) Kebun Raya Purwodadi - Jocelin Andiana; Elga Renjana (Prosiding Seminar Biologi, 2021)
Botanical Gardens is one of the ex situ plant conservation areas, one of them is Purwodadi Botanic Garden (PBG). One of the roles as an inventory is an important basis for assessing biodiversity in a particular area. PBG has a land that is intentionally forested, namely an arboretum (forested area). One of the plant groups that can be found in the PBG’s Arboretum is ferns (Pteridophyta). This study aimed to inventory of ferns in the PBG’s Arboretum completed with their conservation status. The method used in this study was the explorative method by exploring an area followed by observing the target plants. Furthermore, environmental data measurements were also carried out, including temperature, humidity, light intensity and soil pH. Based on the results of the study, were found 11 species, 8 genera, and 7 family of ferns in the PBG’s Arboretum. A total of 8 species of them are Indonesia's native species. Furthermore, two species have been recorded on the IUCN Red List site with the least concern (LC) category, which are Christella dentata and Tectaria. polymorpha. Therefore, it is necessary to conserve ferns, both in situ and ex situ.